Could handling and acclimatization affect biomarker responses in oysters? - Zanette, Juliano; Freitas, Fernanda Almeida de; Silva, Angela Zaccaron da; Moser, Righetto; Almeida, Eduardo Alves de; Marques, Maria Risoleta Freire; Bainy, Celso Dias (Elsevier, 2008)
The aim of this study was to investigate whether handling and acclimatization could affect the biomarker responses in oysters Crassostrea gigas. Adult oysters were sampled in a farming area, subjected to handling stress during two hours (shell cleaning and transport), and then acclimatized in laboratory for 2, 3 and 4 weeks. Groups of five oysters were sampled before and after the handling (T0 and T1, respectively), and after 2, 3 and 4 weeks acclimatization. During the acclimatization, water was renewed daily, food given twice a day and temperature and salinity maintained at 22 °C and 25 ppt, respectively. One group, in another tank, was kept in similar conditions and was exposed for 1 week to 0.1 % diesel after the 2-weeks acclimatization period. After exposure, gills were immediately frozen in liquid N 2 for biochemical analyses. Higher expression of heat-shock proteins (HSP70) was observed after handling, and after acclimatization periods of 3-week and 4-week, compared to the T0 group. The diesel exposed group did not show elevated levels of HSP70, when compared to the 3-week acclimatized group. The activity of glutathione S-transferase (GST) was unchanged after handling, but was lower after all acclimatization periods, compared to the T0 group. Exposure to diesel caused an increase in GST activity compared to the 3-week acclimatized group, but not compared to T0. The activity of catalase (CAT), acetylcholinesterase (AChE), and the MDA levels remained unchanged during the whole experiment. These results point to the need of a special care in laboratory and field experiments employing HSP70 and GST as biomarkers. (Supported by CNPq-CTPetro to ACDB.). © 2008 Published by Elsevier Ltd.